Collateral damage [videorecording (DVD)] - Reuther, Steven; Foster, David, 1929-2019; Roose, Ronald; Griffiths, David, 1952-; Griffiths, Peter, 1950-; Davis, Andrew, 1946-; Schwarzenegger, Arnold; Koteas, Elias, 1961-; Neri, Francesca, 1964-; Curtis, Cliff, 1968-; Leguizamo, John; Turturro, John, 1957-; et al. (Distributed by Warner Home Video, 2009)
Firefighter Gordon Brewer is plunged into the complex and dangerous world of international terrorism after he loses his wife and child in a bombing credited to Claudio 'The Wolf' Perrini. The government feels that they have more important things to be concerned with, so Brewer decides to take things into his own hands. He becomes frustrated and haunted by the thought that the man responsible for murdering his family might never be brought to justice. He tracks his quarry ultimately to Colombia, but discovers that it's not going to be that easy. When a woman and her child get in his way he has to decide just how much like the Wolf he is willing to be in order to gain the vengeance his family deserves.